Analysis of the Impact of Orthogonalized Brent Oil Price Shocks on the Returns of Dependent Industries in Times of the Russian War - Tim Friedhoff; Cam-Duc Au; Philippe Krahnhof (Masaryk University, Faculty of Economics and Administration, 2023)
It has already been literarily proven that the past shows a statistical correlation between crude oil prices and certain industries that are influenced by its volatility. In this context, the Russian war in particular leads to reassessable reactions of these industries. In this paper, we investigate this influence during the war period and compare the results with pre-war calculations for 533 companies from 12 industries. Therefore, we use a recursive SVAR model, based on which we illustrate our results graphically with the impulse-response function. We find that the shock responses of industries to Brent volatilities during the war period have a high explanatory power, but we find different results for the individual industries. While oil-producing industries react positively to positive shocks (more so during the war period), the impact on oil-producing industries is rather small, but negative. Oil & Gas Drilling shows an increase of 10 % and Tires & Rubber Products a decrease of 8 %. Also other industries show surprising results.
Keywords: C22; Q11; 330; Oil price shock; Oil industries; SVAR model; Impulse response function